FAKTOR-FAKTOR YANG MEMENGARUHI PROFITABILITAS PERUSAHAAN ASURANSI JIWA SERTA PERBEDAANNYA SEBELUM DAN SAAT COVID-19 - Lutfia Isnaeni (2023)
This research is a quantitative research that aims to determine the factors that affect the profitability of life insurance companies and their differences before and during Covid-19. This study used by conventional-based life insurance companies registered with the Financial Services Authority and the Indonesian Life Insurance Association for the 2018-2021 period as a sample. Profitability as a dependent variable is proxied by return on assets and the independent variables used are premium growth, claim expenses, and risk-based capital. This study used secondary data in the form of financial statements and company annual reports with a research sample of 39 conventional life insurance companies. The analysis method used is multiple regression analysis and paired sample t-tests with STATA version 13. The results of this study prove that the growth of premiums and claim expenses have a negative and significant effect on profitability. Meanwhile, risk-based capital has no significant effect on profitability. Then, there is no difference in the profitability level of life insurance companies before and during Covid-19.